Against explanation: Dylan Thomas and smudginess. Issue 12 (2nd December 2021) - Cassels, Imogen
ABSTRACT: Dylan Thomas's poems have frequently been subjected to critical glosses which treat his poems almost like puzzles to be solved, or codes to be deciphered. This is a method of reading, however, which diminishes the pleasure and opportunity of his 'difficulty', and belies the complexity and ambiguity that characterise Thomas's work. This article will argue against 'explanations' of Thomas, taking its instead cues from the notes Thomas issued in his correspondence with friends and interested readers to reflect on the uncertainty or 'smudg[iness]' (in William Empson's phrase) of his poetics. This is a more playful way of reading Thomas which embraces his formal habits as well as his semantic ones, to more faithfully represent where his 'difficulty' is generated, and the readerly opportunities it affords.